2005
DOI: 10.1111/j.1365-3040.2005.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of volatile emissions in jasmonate‐deficientspr2tomato mutants favour oviposition by insect herbivores

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 73 publications
8
72
2
Order By: Relevance
“…In OPR3-RNAi plants, monoterpenes and sesquiterpenes were found to be reduced, which is consistent with previous reports on reduced terpene production in the jasmonate-deficient tomato mutants defenseless1 (Thaler et al, 2002;Ament et al, 2004;Degenhardt et al, 2010) and suppressor of prosystemin-mediated response2 (spr2) (Sánchez-Hernández et al, 2006;Wei et al, 2013), as well as in the JA/JA-Ileinsensitive jai1 mutant (Li et al, 2004). Likewise, a reduction in type VI glandular trichome density, similar to the approximately 65% reduction in OPR3-RNAi plants, was also reported for jai1 (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In OPR3-RNAi plants, monoterpenes and sesquiterpenes were found to be reduced, which is consistent with previous reports on reduced terpene production in the jasmonate-deficient tomato mutants defenseless1 (Thaler et al, 2002;Ament et al, 2004;Degenhardt et al, 2010) and suppressor of prosystemin-mediated response2 (spr2) (Sánchez-Hernández et al, 2006;Wei et al, 2013), as well as in the JA/JA-Ileinsensitive jai1 mutant (Li et al, 2004). Likewise, a reduction in type VI glandular trichome density, similar to the approximately 65% reduction in OPR3-RNAi plants, was also reported for jai1 (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…3) was consistent with the susceptibility to B. tabaci observed in plants compromised in JA synthesis or signaling (Sánchez-Hernández et al 2006;Zarate et al 2007). However, the fact that BsDN treatment was active in the above mutants also suggested that mechanism(s) other than those regulated by JA contributed to the ISR against B. tabaci produced by BsDN inoculation.…”
Section: Discussionsupporting
confidence: 77%
“…The amino-acid and carbohydrate levels positively correlated with the density and development of whiteßies (Bi et al 2003). In contrast, the secondary metabolites (i.e., jasmonic acid [JA], salicylic acid [SA], phenolics, and terpenes), deterred the feeding and oviposition of piercingÐsucking insects and decreased their population Þtness (Mansour et al 1997, Jormalainen et al 2001, Pegadaraju et al 2005, Sanchez-Hernandez et al 2006, Zarate et al 2007). Because of alterations in the plant biochemistry after an insect infestation, the settling, feeding, growth, development, and fecundity of later-arriving herbivores may be affected (Inbar et al 1999, Bi et al 2003, Ohgushi 2005.…”
mentioning
confidence: 99%